Evidence for possible role of melatonin in reducing oxidative stress in multiple sclerosis through its effect on SIRT1 and antioxidant enzymes - Emamgholipour, Solaleh; Hossein-nezhad, Arash; Sahraian, Mohammad Ali; Askarisadr, Fatemeh; Ansari, Mohammad (Life sciences (1973), 2016)
Oxidative stress plays a crucial role in the pathogenesis of multiple sclerosis (MS). Melatonin has a central role in the modulation of oxidative stress pathways. We aimed to investigate the effect of melatonin on mRNA expression and activity of sirtuin1 (SIRT1) and its target genes, manganese superoxide dismutase (MnSOD), and catalase in peripheral blood mononuclear cells (PBMCs) from MS patients and healthy subjects. This study was performed on 12 patients with relapsing–remitting MS (RRMS) and 14 age- and sex-matched healthy subjects. PBMCs were isolated and treated with pharmacological concentration of melatonin (1mM) for 12h. Gene expression was evaluated by real time-PCR. SIRT1 activity in PBMCs was measured using a fluorometric assay. MnSOD and catalase activities in PBMCs were determined by colorimetric assays. Plasma total antioxidant capacity was measured using the ferric reducing ability of plasma assay. Melatonin significantly increased activities and mRNA levels of SIRT1 and catalase in both patients and healthy subjects, whereas melatonin treatment caused a pronounced increase in MnSOD mRNA expression and activity only in patients. In MS patients, SIRT1 activity did not correlate with catalase and MnSOD activities before melatonin treatment, while a significant correlation was observed between SIRT1 activity and catalase activity in PBMCs of patients after melatonin treatment. It appears that the antioxidant status is affected in PBMCs from MS patients and melatonin could improve impaired antioxidant defense in MS through upregulation of SIRT1, MnSOD and catalase, which might be important in MS management.